Data driven analysis using fuzzy time series for air quality management in Surabaya - Didiet Darmawan; Mohammad Isa Irawan; Arie Dipareza Syafei (Sustinere: Journal of Environment and Sustainability, 2017)
One of the environmental issues that can affect human health is air pollution. As the second largest city in Indonesia, economic development and infrastructure construction in the city of Surabaya led to the increasing role of industrial and motor vehicle use which is proportional to the increase in fuel oil consumption. This condition ultimately led to declining air quality. Gas pollutants that contribute to air pollution such as CO, SO2, O3, NO2 and particulate matter PM10 are pollutants that have a direct impact on health. This study aims to analyze, monitor and predict air pollutant concentrations recorded by the Environment Agency Surabaya City based on time series with Fuzzy Time Series.MAPE calculation results on the parameters of pollutants are NO2: 23.6%, CO: 19.5%, O3: 22.75%, PM10: 9.96% and SO2: 3.6%.